2016
DOI: 10.1177/1541204015609965
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerating Youth With Mental Health Problems

Abstract: Mental health problems among youth in the juvenile justice system are of particular concern given their high prevalence rate. The current study applies attribution theory and focal concerns to examine how mental health problems influence the judicial decision to commit youth to confinement. Furthermore, the study examines whether the effect of mental health problems is conditioned by race and ethnicity, hypothesizing that minorities with mental health problems will be treated more severely than Whites with men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 97 publications
0
14
2
Order By: Relevance
“…Healthier families can reduce risk for children to have behavior problems and legal issues. White (2016) determined that African American children with mental health problems receive more severe treatment from the juvenile justice system. She speculated this may be due to judges' implicit racial biases and negative stereotypes, as they may erroneously ascribe negative attributes to African American and feel that these youth are dangerous and need to be held accountable for their actions (White, 2016).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthier families can reduce risk for children to have behavior problems and legal issues. White (2016) determined that African American children with mental health problems receive more severe treatment from the juvenile justice system. She speculated this may be due to judges' implicit racial biases and negative stereotypes, as they may erroneously ascribe negative attributes to African American and feel that these youth are dangerous and need to be held accountable for their actions (White, 2016).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…White (2016) determined that African American children with mental health problems receive more severe treatment from the juvenile justice system. She speculated this may be due to judges' implicit racial biases and negative stereotypes, as they may erroneously ascribe negative attributes to African American and feel that these youth are dangerous and need to be held accountable for their actions (White, 2016). Alternatively, judges may feel it is the state's responsibility to intervene so that children of color get the treatment they need, doubting that the families and impoverished neighborhoods would be capable of fulfilling those needs.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Child functioning is likely to be related to a youth’s level of involvement with the juvenile justice system. Mental health need and past traumatic experiences have been found to be associated with more severe juvenile justice sanctions (Espinosa et al, 2013; White, 2016). Juvenile justice youth in detention report higher rates of mental health disorders (Abram, Teplin, McClelland, & Dulcan, 2003; Teplin, Abram, McClelland, Dulcan, & Mericle, 2002), while youth with unmet social service needs were more likely to be involved in the juvenile justice system than in other public systems (Hazen, Hough, Landsverk, & Wood, 2004; Maschi, Hatcher, Schwalbe, & Rosato, 2008).…”
Section: Potential Difference In Institutional Placementmentioning
confidence: 99%
“…It is possible that certain subgroups of youth are more likely to experience certain patterns of institutional placement. Thus, this study also examines how extralegal factors such as family status, mental health, and substance use are related to the different patterns of institutional placement (Fader, Harris, Jones, & Poulin, 2001; McCoy, Walker, & Rodney, 2012; White, 2016). We explore how demographic, legal, and extralegal factors distinguish among these groups.…”
mentioning
confidence: 99%
“…Griner and Smith (2006), in their seminal meta-analytic review, showed that culturally adapted mental health interventions were 4 times more effective when tailored to one cultural group versus to clients from a variety of cultural backgrounds. It has been documented that White youth prior to and upon contact with the justice system receive psychiatric services at much higher rates than do Latinx youth (White, 2016), even when the behavioral health needs are equivalent to those of other ethnicities and races (Winkelman et al, 2017). Rather than basing all services on the needs of White youth, research that provides a nuanced understanding of trauma exposure as it relates to the Latinx community, and by gender in particular, is warranted.…”
mentioning
confidence: 99%